1995
DOI: 10.1111/j.1365-2265.1995.tb02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in primary hyperparathyroidism in India

Abstract: Patients with primary hyperparathyroidism in India presented with bone and renal diseases; half were normocalcaemic. All the patients had hypercalciuria despite the bone disease. The PTH-MM levels were increased and 25-OHD3 levels were low. The predominant bone disease is probably due to prolonged primary hyperparathyroidism coexisting with low calcium intake and/or 25-OHD3 deficiency. The mean weight of the adenoma was higher than that reported for patients in the Western literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
110
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 21 publications
8
110
6
Order By: Relevance
“…In 1973, Hodgkin first published data regarding vitamin D deficiency [10]. Between 1995 and 2000, studies from north India proved the deficiency of vitamin D in our population [11,12].Subsequently south Indian studies also confirmed it [13][14][15][16].…”
Section: Introductionmentioning
confidence: 81%
“…In 1973, Hodgkin first published data regarding vitamin D deficiency [10]. Between 1995 and 2000, studies from north India proved the deficiency of vitamin D in our population [11,12].Subsequently south Indian studies also confirmed it [13][14][15][16].…”
Section: Introductionmentioning
confidence: 81%
“…Diagnosis is made in symptomatic patients following investigations as seen in studies by Biyabani, [9] Younes, [13] Norris [16] and Bhansali [10]. Vit Defi ciency found in endemic area of some developing countries aggravates the osteitis fi brosa cystic and other related disorder in PHPT [4,14]. Male : female ratio described in literature is 1:2 or 1:3, [2,6,7,11,15,16] in western world, while in our series as also in other series in India and other oriental countries male /female ratio is 1:4 or more [9,4,5,14,17] .The disease appears to present at a comparatively young age (below 40 years) in India and eastern countries.…”
Section: Discussionmentioning
confidence: 99%
“…A large study of primary hyperthyroidism at Mayo clinic of 10 years follow up failed to answer if surgery is necessary in asymptomatic patients [13]. Symptomatic PHPT is still the predominant form of the disease in developing countries [4,5,6,14]. Clinical presentation of skeletal manifestation, abdominal pain, renal calculi with urinary symptoms, gastrointestinal and cardiac symptoms, anxiety, depression and sleeplessness are found in various percentage in PHPT.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of bone disease in patients with PHPT in developing countries has been attributed to associated vitamin D and dietary calcium deficiency (Harinarayan, 1995). The various classical clinical features are summed up in [ Table 2].…”
Section: Symptomatic Phptmentioning
confidence: 99%